2007
DOI: 10.1089/gyn.2007.b-02276-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Massage on Intra- and Postoperative Outcomes

Abstract: The aim of this study was to investigate the effects of preoperative massage on intra-and postoperative outcomes in 105 female subjects who had a laparoscopic gynecologic surgery procedure done. The subjects received a 30-minute massage (massage group) or 30 minutes of passive touch (control group). There was no difference between the groups in the average dose of inhaled anesthetics received. Patients in the massage group received significantly less intraoperative narcotics (2.2 ؎ 1.1 versus 2.8 ؎ 2.0 mcg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In congruent with these findings, a quasi-experimental research approach was used to determine the effect of ten minute foot massage in reduction of post-operative pain and the psychological response of the patient. The result indicates a significant difference in the pre and post massage pain score and the findings of the opinionnaire showed that 80-90% of the patients expressed a positive opinion of foot massage which shows a high acceptability rate [12] .…”
Section: Discussionmentioning
confidence: 90%
“…In congruent with these findings, a quasi-experimental research approach was used to determine the effect of ten minute foot massage in reduction of post-operative pain and the psychological response of the patient. The result indicates a significant difference in the pre and post massage pain score and the findings of the opinionnaire showed that 80-90% of the patients expressed a positive opinion of foot massage which shows a high acceptability rate [12] .…”
Section: Discussionmentioning
confidence: 90%
“…Researchers have shown that massage works on a cellular level to decrease inflammation and increase the energy-producing organelles of muscle 15. McRee et al16 found the immediate response to massage was equivalent to a dose of morphine to improve sleep and decrease anxiety in women after gynecologic surgery. The Gate Control Theory proposes a gating mechanism at the level of the spinal cord and may explain the effects of massage on perception of pain 17.…”
Section: Physiological Effectsmentioning
confidence: 99%